The Palgrave Handbook of Workplace Spirituality and Fulfillment (Springer International Publishing, 2018)
This book presents an up-to-date and comprehensive survey of the field of Workplace Spirituality. It uses a structured yet open-ended schema to capture the best of research and practices on the subject. Presenting a clear and concise approach to spirituality in the workplace, it traces the genesis and growth of this burgeoning field and suggests trends and future directions in Workplace Spirituality. Drawing upon various theistic and non-theistic traditions of the world, it negotiates a clear dialectic of different dimensions and models of Workplace Spirituality, including the best of emerging new age spiritualties. Weaving various strands of management, spirituality, religion, and positive psychology in a systematic manner, this Handbook provides an in-depth and critical appraisal of a wide array of topics such as: spiritual, social, and emotional intelligence; mindfulness, meaning and purpose and fulfillment at work; various forms of positive leadership such as servant, values-based, authentic, spiritual leadership; servant-followership and corporate citizenship behavior; workplace spirituality and organizational performance.